Antagonistic effects of temperature and salinity on total dimethylsulfoniopropionate (DMSPt) production in a river-dominated bay during extreme winter events - Lingxiao Li; Jing Sun; Zhengguo Cui; Tao Jiang; Zhenhao Liu; Keming Qu; Hongsheng Wang; Qingjing Hu; Hongwu Cui; Shenghui Zhang (Estuarine, Coastal and Shelf Science, 2026)

Fasudil attenuates fluoride-induced neuronal synaptic damage by inhibiting microglial inflammation - Wenjing Yang; Keming Bu; Xiaohan Ren; Shaoxiao Qin; Sheng Wang; Fang Chu; Chunqing Lu; Zhipeng Liu; Jiaying Liu; Yuqi Zhang; Xiyue Yang; Yanhui Gao; et al. (Environmental Toxicology and Pharmacology, 2026)

Environmental controls and nonlinear responses of the diatom-dinoflagellate ratio in Jiaozhou Bay - Yipeng Huang; Zhengguo Cui; Changhua Liu; Dongsheng Ding; Lin Zhu; Keming Qu; Yuqiu Wei; Jun Sun (Marine Pollution Bulletin, 2026)

IP3R1 regulates AMPK-mTOR-mediated mitochondrial function to influence the oocyte-to-embryo transition of porcine - Ran Teng; Ning Xu; Xingfu Chen; Yuening Xing; Xiaoqing Sun; Dexin Yuan; Keming Huang; Lepeng Gao; Suo Li (Theriogenology, 2026)

Corrigendum to “Rapid and scalable synthesis of CALF-20 extrudates for VPSA-based CO2 capture” [Chem. Eng. J. 527 (2026) 171623] - Jifu Wang; Jianyu Sun; Lina Zhang; Guoping Hu; Gaobing Sheng; Keming Chen; Tianyang Zhu; Yufeng Hao; Hongyu Zhao; Baodeng Wang; Wei Wei; Nannan Sun (Chemical Engineering Journal, 2026)

Engineering high-fertility synthetic apomixis in hybrid rice via genome editing of MiMe and OspPLAIIκ - Chaolei Liu; Yuye Chen; Tingting Sun; Jian Wang; Huan Liang; Keming Zhu; Qian Qian; Kejian Wang (Science China Life Sciences, 2026)

How does vegetation invasion reshape bird communities? Insights from mangrove and Spartina alterniflora saltmarsh in coastal China - Qingyan Sun; Xueman Xing; Keming Ma (Journal of Environmental Management, 2026)

Significant effects of temperature and pH on zooplankton dynamics: Implications for ocean warming and acidification - Minghao Li; Dongsheng Ding; Chuanxia Liu; Zhengguo Cui; Wei Dong; Jun Sun; Keming Qu; Yuqiu Wei (Ocean & Coastal Management, 2026)

Rapid and scalable synthesis of CALF-20 extrudates for VPSA-based CO2 capture - Jifu Wang; Jianyu Sun; Lina Zhang; Guoping Hu; Gaobing Sheng; Keming Chen; Tianyang Zhu; Yufeng Hao; Hongyu Zhao; Baodeng Wang; Wei Wei; Nannan Sun (Chemical Engineering Journal, 2026)

Synergistic effect of Cu-Ni bimetallic doping in Cd0.8Zn0.2S for enhanced photocatalytic CO2 reduction: Modulating the d-band center for improved activity - Haonan Li; Keming Li; Shuhan Sun; Yongjia Zhang; Zhanfeng Li; Yanting Tian (Journal of Environmental Chemical Engineering, 2025)

Significance of temperature and salinity in the dynamics of diatoms and dinoflagellates along the coastal Yellow Sea - Chenshi Weng; Dongsheng Ding; Qian Yang; Lin Zhu; Jun Sun; Keming Qu; Zhengguo Cui; Yuqiu Wei (Progress in Oceanography, 2025)

Predatory protist promotes disease suppression against bacterial wilt through enriching plant beneficial microbes at the early stage of plant growth - Yuqi Song; Chen Liu; Keming Yang; Shiqi Sun; Lin Wang; Cansheng Yuan; Yangchun Xu; Wu Xiong; Qirong Shen; Zhong Wei (Plant and Soil, 2025)

Sedimentary heavy metal interactions with phytoplankton and zooplankton across the Bohai Sea - Yuqiu Wei; Lun Song; Yuanqing Ma; Jiandong Mu; Wei Yi; Jun Sun; Keming Qu; Zhengguo Cui (Journal of Environmental Management, 2025)

Context dependence masks the long-term harm of Spartina alterniflora invasion on macrobenthos in China - Qingyan Sun; Keming Ma (Journal of Environmental Management, 2025)

Implications of seawater characteristics on dissolved heavy metals in near-shore surface waters of the Yellow Sea - Minghao Li; Dongsheng Ding; Yong Xu; Qian Yang; Jun Sun; Keming Qu; Zhengguo Cui; Yuqiu Wei (Marine Pollution Bulletin, 2025)

Implications of ocean warming and acidification on heavy metals in surface seawater of the Bohai Sea - Yuqiu Wei; Lun Song; Yuanqing Ma; Jiandong Mu; Wei Yi; Jun Sun; Keming Qu; Zhengguo Cui (Journal of Hazardous Materials, 2024)

Bioaccumulation of polycyclic aromatic hydrocarbons and their human health risks depend on the characteristics of microplastics in marine organisms of Sanggou Bay, China - Qi Sui; Xiaobin Yang; Xuemei Sun; Lin Zhu; Xinguo Zhao; Zhihua Feng; Bin Xia; Keming Qu (Journal of Hazardous Materials, 2024)

Temperature and nutrients drive distinct successions between diatoms and dinoflagellates over the past 40 years: Implications for climate warming and eutrophication - Yuqiu Wei; Qingshan Luan; Xiujuan Shan; Hongwu Cui; Keming Qu; Zhengguo Cui; Jun Sun (Science of The Total Environment, 2024)

Strength characteristics and carbonation depth evolution of modified magnesium slag based solid waste storage backfill materials - Zhiyu Fang; Lang Liu; Wei He; Keming Han; Hang Lan; Yuheng Gao; Weiji Sun; Zhen Han; Lei Xia; Pengyu Yang (Journal of Environmental Chemical Engineering, 2024)

Physiological and transcriptomic analysis reveals the toxic and protective mechanisms of marine microalga Chlorella pyrenoidosa in response to TiO2 nanoparticles and UV-B radiation - Lin Zhu; Sulan Feng; Yu Li; Xuemei Sun; Qi Sui; Bijuan Chen; Keming Qu; Bin Xia (Science of The Total Environment, 2024)

Polystyrene nanoplastics affected the nutritional quality of Chlamys farreri through disturbing the function of gills and physiological metabolism: Comparison with microplastics - Yejiao Sun; Xinguo Zhao; Qi Sui; Xuemei Sun; Lin Zhu; Andy M. Booth; Bijuan Chen; Keming Qu; Bin Xia (Science of The Total Environment, 2024)

Environmental forcing of phytoplankton carbon-to-diversity ratio and carbon-to-chlorophyll ratio: A case study in Jiaozhou Bay, the Yellow Sea - Yingzhe Wang; Zhengguo Cui; Dongsheng Ding; Qian Yang; Lin Zhu; Keming Qu; Jun Sun; Yuqiu Wei (Marine Pollution Bulletin, 2023)

New insights into the impact of polystyrene micro/nanoplastics on the nutritional quality of marine jacopever (Sebastes schlegelii) - Xuemei Sun; Xuru Wang; Andy M. Booth; Lin Zhu; Qi Sui; Bijuan Chen; Keming Qu; Bin Xia (Science of The Total Environment, 2023)

Carbonation curing of modified magnesium-coal based solid waste backfill material for CO2 sequestration - Zhiyu Fang; Lang Liu; Xiaoyan Zhang; Keming Han; Jingyu Wang; Mengbo Zhu; Weiji Sun; Wei He; Yuheng Gao (Process Safety and Environmental Protection, 2023)

Fine mapping and candidate gene analysis of qSB12YSB, a gene conferring major quantitative resistance to rice sheath blight - Yu Wang; Quanyi Sun; Jianhua Zhao; Taixuan Liu; Haibo Du; Wenfeng Shan; Keting Wu; Xiang Xue; Chao Yang; Jun Liu; Zongxiang Chen; Keming Hu; et al. (Theoretical and Applied Genetics, 2023)

RIN enhances plant disease resistance via root exudate-mediated assembly of disease-suppressive rhizosphere microbiota - Keming Yang; Ruixin Fu; Haichao Feng; Gaofei Jiang; Omri Finkel; Tianyu Sun; Mingchun Liu; Baowen Huang; Shan Li; Xiaofang Wang; Tianjie Yang; Yikui Wang; et al. (Molecular Plant, 2023)

Picocyanobacteria–A non-negligible group for the export of biomineral silica to ocean depth - Yuqiu Wei; Keming Qu; Zhengguo Cui; Jun Sun (Journal of Environmental Management, 2023)

Key determinants controlling the seasonal variation of coastal zooplankton communities: A case study along the Yellow Sea - Yuqiu Wei; Xueyang Chen; Ying Liu; Yingzhe Wang; Keming Qu; Jun Sun; Zhengguo Cui (Marine Pollution Bulletin, 2023)

Ocean acidification enhances the embryotoxicity of CuO nanoparticles to Oryzias melastigma - Hao Wang; Qi Sui; Jian Zhao; Xuemei Sun; Lin Zhu; Bijuan Chen; Keming Qu; Bin Xia (Journal of Hazardous Materials, 2023)

Charge-dependent negative effects of polystyrene nanoplastics on Oryzias melastigma under ocean acidification conditions - Yufei Chen; Xia Wang; Qi Sui; Guozhu Chang; Xuemei Sun; Lin Zhu; Bijuan Chen; Keming Qu; Bin Xia (Science of The Total Environment, 2023)

Ocean acidification and warming significantly affect coastal eutrophication and organic pollution: A case study in the Bohai Sea - Yuqiu Wei; Dongsheng Ding; Ting Gu; Yong Xu; Xuemei Sun; Keming Qu; Jun Sun; Zhengguo Cui (Marine Pollution Bulletin, 2023)

Ecological risk assessment of metallic nanoparticles on the marine environments: Species sensitivity distributions analysis - Sulan Feng; Lin Zhu; Xinguo Zhao; Qi Sui; Xuemei Sun; Bijuan Chen; Keming Qu; Bin Xia (Frontiers in Marine Science, 2022)
Metallic nanoparticles (NPs) are increasingly being used and inevitably entering the marine environment. Therefore, the adverse effects of NPs on individual marine species have attracted increasing attentions. However, to date, the ecological risks of NPs on the marine ecosystem remain poorly understood. In this study, species sensitivity distributions (SSDs) were constructed for Ag, ZnO, CuO, and TiO 2 NPs to understand their ecotoxicity to the marine ecosystem and the contribution of size effect and ion effect to the nanotoxicity. Furthermore, a case study on the assessment of marine ecological risk and marine environment carrying capacity of metallic NPs was performed in Jiaozhou Bay, China. The results showed the toxicity of metallic NPs to marine species following the order of Ag > ZnO > CuO > TiO 2 . Both size effect and ion effect contributed to the toxicity of NPs. Environmental concentrations of Ag, ZnO, CuO, and TiO 2 NPs are much lower than the predicted no-effect concentrations, indicating that these metallic NPs have not yet posed risks to the marine ecosystem based on currently limited measured environmental concentrations of metallic NPs in seawater. And the marine environment carrying capacity of Ag, ZnO, CuO, and TiO 2 NPs in Jiaozhou Bay seawater were determined to be 5.03, 8.72, 93.06, and 629.79 t, respectively. The results help us understand the ecological risk of NPs in marine environments and provide a scientific basis for the sustainable development of nanotechnology.

Mussel Byssal Attachment Weakened by Anthropogenic Noise - Xinguo Zhao; Shuge Sun; Wei Shi; Xuemei Sun; Yan Zhang; Lin Zhu; Qi Sui; Bin Xia; Keming Qu; Bijuan Chen; Guangxu Liu (Frontiers in Marine Science, 2021)
The increasing underwater noise generated by anthropogenic activities has been widely recognized as a significant and pervasive pollution in the marine environment. Marine mussels are a family of sessile bivalves that attach to solid surfaces via the byssal threads. They are widely distributed along worldwide coastal areas and are of great ecological and socio-economic importance. Studies found that anthropogenic noise negatively affected many biological processes and/or functions of marine organisms. However, to date, the potential impacts of anthropogenic noise on mussel byssal attachment remain unknown. Here, the thick shell mussels Mytilus coruscus were exposed to an ambient underwater condition (∼50 dB re 1 μPa) or the playbacks of pile-driving noise (∼70 or ∼100 dB re 1 μPa) for 10 days. Results showed that the noise significantly reduced the secretion of byssal threads (e.g., diameter and volume) and weakened their mechanical performances (e.g., strength, extensibility, breaking stress, toughness and failure location), leading to a 16.95–44.50% decrease in mussel byssal attachment strength. The noise also significantly down-regulated the genes expressions of seven structural proteins (e.g., mfp-1, mfp-2, mfp-3, mfp-6, preCOL-P, preCOL-NG, and preCOL-D) of byssal threads, probably mediating the weakened byssal attachment. Given the essential functions of strong byssal attachment, the findings demonstrate that the increasing underwater anthropogenic noise are posing a great threat to mussel population, mussel-bed community and mussel aquaculture industry. We thus suggest that future work is required to deepen our understanding of the impacts of anthropogenic noise on marine invertebrates, especially these with limited locomotion ability, like bivalves.

Environmental factors affecting regional differences and decadal variations in the buried flux of marine organic carbon in eastern shelf sea areas of China - Qian Yang; Keming Qu; Shu Yang; Yao Sun; Yan Zhang; Mingying Zhou (Acta Oceanologica Sinica, 2021)

Magnesium alleviates aluminum toxicity by promoting polar auxin transport and distribution and root alkalization in the root apex in populus - Zhen Zhang; Dunyi Liu; Hongjun Meng; Shengting Li; Shufeng Wang; Zhongchun Xiao; Juanjuan Sun; Longran Chang; Keming Luo; Nannan Li (Plant and Soil, 2020)

Coccolithophore responses to the Pacific Decadal Oscillation in the East China Sea region of the Northwest Pacific from ad 1901 to 2013 - Shu Yang; Mingli Yuan; Qian Yang; Jiansheng Huang; Mengran Sun; Jun Sun; Keming Qu; Yao Sun (Journal of Quaternary Science, 2019)
A high‐resolution study of coccolithophores in a sediment core from the East China Sea (ECS) region of the Northwest Pacific revealed that fluctuations in coccolithophore assemblages responded well to the Pacific Decadal Oscillation (PDO) during 1901–2013. Emiliania huxleyi and Gephyrocapsa oceanica were the most dominant species, accounting for more than 97% of all the ten detected species. The variation of the two dominant species showed a significant positive correlation, and they both increased during peak values of the PDO. Decreased stratification and increased nutrient supplementation from the bottom water induced by lower sea surface temperatures in the ECS, which were associated with high PDO values, were responsible for the dominant coccolithophore increase. Similarly, the increase of Calcidiscus leptoporus also corresponded to low‐temperature and high‐nutrient conditions associated with the cold phase in the ECS (positive phase of the PDO). The responses of decadal C. leptoporus variations to changes in cold and warm phases of the PDO in the Northwest and Northeast Pacific indicate that C. leptoporus preserved in sediment cores represents a potential indicator for reconstructing phase changes of the PDO during ancient times.

A novel approach to evaluate potential risk of organic enrichment in marine aquaculture farms: a case study in Sanggou Bay - Shu Yang; Qian Yang; Xianli Song; Sai Liu; Keming Qu; Yao Sun (Environmental Science and Pollution Research, 2018)

The effect of mechanical stretch stress on the differentiation and apoptosis of human growth plate chondrocytes - Keming Sun; Fangna Liu; Junjian Wang; Zhanhao Guo; Zejuan Ji; Manye Yao (In Vitro Cellular & Developmental Biology - Animal, 2017)

Burial fluxes and sources of organic carbon in sediments of the central Yellow Sea mud area over the past 200 years - Shu Yang; Qian Yang; Sai Liu; Deling Cai; Keming Qu; Yao Sun (Acta Oceanologica Sinica, 2015)

A poplar R2R3-MYB transcription factor, PtrMYB152, is involved in regulation of lignin biosynthesis during secondary cell wall formation - Chaofeng Li; Xianqiang Wang; Wanxiang Lu; Rui Liu; Qiaoyan Tian; Yiming Sun; Keming Luo (Plant Cell, Tissue and Organ Culture (PCTOC), 2014)

Isolation and promoter analysis of a chalcone synthase gene PtrCHS4 from Populus trichocarpa - Yiming Sun; Qiaoyan Tian; Li Yuan; Yuanzhong Jiang; Yan Huang; Min Sun; Shaohu Tang; Keming Luo (Plant Cell Reports, 2011)

The chitinase gene (Bbchit1) from Beauveria bassiana enhances resistance to Cytospora chrysosperma in Populus tomentosa Carr. - Zhichun Jia; Yimin Sun; Li Yuan; Qiaoyan Tian; Keming Luo (Biotechnology Letters, 2010)

Excision of selectable marker gene from transgenic tobacco using the GM-gene-deletor system regulated by a heat-inducible promoter - Keming Luo; Min Sun; Wei Deng; Shan Xu (Biotechnology Letters, 2008)